Psychological significance of the period before higher education in teaching a foreign language - Karimova, Nigina (Science and Education, 2023)
In our article, the peculiarities of pedagogical methods, the role of language learning games in the course of the lesson, the participation of group members, the effective conduct of games, the development of foreign language learning in young students, the teacher and strengthening of student-student relations, multifaceted and psychological aspects of communication are discussed.